Nanosilicon application changes the morphological attributes and essential oil compositions of hemp (Cannabis sativa L.) under water deficit stress - Ayyub Rezghiyan; Hassan Esmaeili; Mohsen Farzaneh (Scientific Reports)
Abstract Various practical strategies have been employed to mitigate the detrimental effects of water deficit stress on plants such as application of nano-stimulants. Nanosilicon plays a crucial role in alleviating the deleterious impacts of both abiotic and biotic stresses in plants by modulating various phyto-morphological and physiological processes. This study aimed to examine the combined effects of drought stress and nanosilicon application on the morphological traits and essential oil content and compositions of hemp (Cannabis sativa L.), in which four-week-old seedlings were subjected to irrigation treatments at four levels, including 100% (control), 80% (mild stress), 60% (moderate stress) and 40% (severe stress) field capacity and nanosilicon at three concentrations (0, 0.5 and 1.5 mM) in a completely randomized factorial design experiment with three replications for 40 days. The results showed that the maximum plant height (109.07 cm), number of nodes (33.3), and number of flowering branches (29.4) were recorded under the treatment of 1.5 mM nanosilicon and 100% FC. The lowest fresh and dry weights of aerial parts were associated to the severe drought stress (40% FC) without nanosilicon application. The mild water stress (80% FC) combined with foliar application of 1.5 mM nanosilicon led to highest EO content (0.17%) compared with the other treatments. However, the highest content of cannabidiol in the essential oil was achieved in the severe water stress (40% FC) and treatment of 0.5 mM nanosilicon. The results showed that the application of nanosilicon improved the morphological characteristics and also changed the content and compositions of the hemp plants under drought stress conditions.